Integrasi peran orang tua dan guru madrasah dalam pembiasaan salat anak usia sekolah dasar: Studi kualitatif di Dusun Ladan Lamongan - Kusnul Widianto; Muhid Muhid (Al-Liqo: Jurnal Pendidikan Islam, 2026)
This study examines the integration of parents’ and teachers’ roles in children’s prayer habituation at Madrasah Diniyah Takmiliyah Al Hidayah Laladan from the perspective of Prophetic Hadiths. Using a qualitative case study approach, data were collected through observation, interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that parents and teachers jointly function as role models, motivators, mentors, and supervisors in fostering prayer habits. Their role integration is implemented through continuous communication, collaborative guidance, and the monitoring of students’ five daily prayers. This synergy strengthens the consistency of prayer practice and promotes children’s spiritual awareness. In the perspective of Prophetic Hadiths, prayer discipline is developed through habituation, exemplary conduct, and supervision carried out collaboratively by parents and teachers. The study concludes that successful prayer habituation depends on the sustained integration of both roles.